Intensitas Pengguna Media Sosial Dengan Gaya Hidup Hedonisme Ibu – Ibu Muda - Miftahul Aula Sa'adah; Najminnur Hasanatun Nida (Universitas Darul Ulum, 2022)
The purpose of this study is to find out if there is a link between the intensity of social media users and the lifestyle of hedonism among young mothers. Sampling method was taken as many as 50 subjects from young mothers aged 20-35 engaged with social media platform. This study used two scales, the intensity scale of social media users with 46 items and the hedonism lifestyle scale with 52 items. Testing the validity of measuring instruments using the SPSS application. Test reliability used is Cronbach's Alpha, resulted coefficient of the hedonism lifestyle scale 0.891 and the intensity scale of social media users revealed 0.970. This study tested with Correlation Spearman Rho. Hypothesis Test obtained a correlation coefficient with p Significant correlation = 0.012 ( < 0.05) . This shows that there is a positive correlation between the Intensity of social media users (young mothers) and the lifestyle of Hedonism.